Apresiasi Guru, Motivasi, Manajemen Kelas Dan Minat Belajar Siswa Terhadap Prestasi Belajar Siswa SMP Budi Utomo Jatipurno Wonogiri - Zulfa Aurellye Oldra Syifaya; Kartika Hendra Titisari; Bambang Mursito (Indo Publishing, 2025)
Problem in this research, student learning achievement is not optimal because many average scores are still below the minimum standard (KKM). This indicator is an important indicator for knowing the determinant factors that influence it. The objectives of this research are: (1) to analyze the influence of teacher appreciation on learning achievement. (2) to analyze the influence of learning motivation on learning achievement. (3) to analyze the influence of classroom management on learning achievement. (4) to analyze the influence of learning interest on learning achievement. The research object was Budi Utomo Jatipuro Wonogiri Middle School, with a sample size of 95 students drawn proportionally. Data for all variables were collected using a questionnaire with five alternative answers. The instrument used met the established standards for validity and reliability, and the research data also met the classical assumption test. Multiple linear regression was the data analysis technique used. The research results show that: (1) teacher appreciation significantly influences learning achievement. (2) learning motivation significantly influences learning achievement. (3) classroom management significantly influences learning achievement. (4) learning interest significantly influences learning achievement.